FORMULASI SARI BUAH TOMAT VARIETAS APEL (Lycopersicum esculentum Mill Pyriforme) SEBAGAI KRIM MASKER - A. Muflihunna (As-Syifaa Jurnal Farmasi, 2012)
An research has been done about formulation of tomato essence (Lycopersicum esculentum Mill) as a Cream Mask by using variation concentration of nonionic emulgator (polysorbat 20 and sorbitan monostearic) that were  formula A (concentration 4%), formula B (concentration 3%), and formula C (concentration 2%). There aim of investigation was to determine the Formulation which has an optimum stability. Stability evaluation has done by observation of organoleptic, creaming volume, dispersed globule, viscosity and yield value, and emulsion type determination before and after stress condition at 50C and 350C for 10 cycles. Observation’s result shown that there wasn’t change before and after stress condition of orgenoleptic, creaming volume, emulsion type, rheology type before and after stress condition. Statistic analyse result of parameter viscosity and yield value by means of random black design shown that formula B (concentration 3%) obtained apparent indifferent in dispersed globule, viscosity and yield value between before and after stress condition. The conclusion that cream mask has the most optimal stability is that by formula B (concentration 3%).Key Words : Formulation, Cream Mask, Tomato essence